Design proximity coupler fed technique with defected ground structure (DGS) effects / Musfirah Hilmi - Hilmi, Musfirah (2013)
Use of defected ground structure (DGS) to enhance performance of the antenna is presented in this paper. Initially, a single patch antenna is designed using proximity coupler fed technique. Then, the experimental investigations have been carried out on a single patch antenna that has been added with a DGS. In order to reduce size of the antenna, an arrow head shaped DGS is used in the ground plane. Analysis has been done to compare between the simulation and the measurement result for antenna with and without DGS. It was found that about 59.3% size of antenna has been reduced.